The Compactness Theorem of SBVH() in the Heisenberg Group Hn (Journal of Partial Differential Equations, 2003)
" In this paper we aim to show a compactness theorem for SBV_H(\u03a9) of special functions u with bounded variation and with \u2207^c_Hu = 0 in the Heisenberg group H^n."
Keywords: SBV_H(Ω) function; Heisenberg group; decomposition of Radon measure; compactness theorem